Comment on “Dealing with the gray zones in the management of gastric cancer: The consensus statement of the İstanbul Group” - Hasbahçeci, Mustafa (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Hasbahçeci M. Comment on “Dealing with the gray zones in the management of gastric cancer: The consensus statement of the İstanbul Group”. Turk J Gastroenterol 2020; 31(11): 838-9.